A polyaniline-derived iron–nitrogen–carbon nanorod network anchored on graphene as a cost-effective air-cathode electrocatalyst for microbial fuel cells. Issue 11 (20th October 2017) - Cao, Chun; Wei, Liling; Wang, Gang; Liu, Jianting; Zhai, Qiran; Shen, Jianquan
Abstract : A cost-effective Fe–N–C/G, which exhibited a distinct catalytic activity in neutral medium and air-cathode MFCs, was prepared for ORR catalyst. Abstract : A highly active and cost-effective Pt-free catalyst for oxygen reduction reaction (ORR) is significantly important for air-cathode microbial fuel cells (MFCs). In this study, a novel low-cost iron–nitrogen–carbon nanorod network-anchored graphene (Fe–N–C/G) nanohybrid was prepared for use as an efficient ORR catalyst. The morphology, chemical composition, and ORR catalytic activity of the as-prepared Fe–N–C/G were investigated by a series physical measurements and electrochemical tests. Finally, it the nanohybrid was employed as an ORR electrocatalyst in the practical air-cathode MFCs. Remarkably, Fe–N–C/G exhibited a comparable catalytic performance and stability in a neutral medium along with even better power generation performance (1601 ± 59 mW m −2 ) in MFCs as compared to the-state-of-the-art Pt/C catalyst (1468 ± 58 mW m −2 ). The superior ORR activity of Fe–N–C/G should be attributed to its N/Fe co-doping, the introduction of graphene, as well as the unique micro-nano structure, which can dramatically favor the oxygen reduction kinetics. Therefore, the cost-effective Fe–N–C/G can be one of the most promising ORR catalysts for application in a neutral medium and practical air-cathode MFCs.